2022
DOI: 10.3389/fpls.2022.950947
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Correlation Between Physiological Characteristics of Rhododendron simsii and Soil Microbial Communities Under Heat Stress

Abstract: The relationship between Rhododendron simsii and its soil microbial community under heat stress was not clear. In this study, the effects of heat stress on the physiological characteristics, soil physicochemical properties and soil microbial community structure of R. simsii were investigated. The experimental control (CK) was set as day/night (14/10 h) 25/20°C and experimental treatments were set as light heat stress (LHS) 35/30°C and high heat stress (HHS) 40/35°C. Our results showed that, compared with CK, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Studies have shown that heat stress significantly reduced the content of carbon, N, and phosphorus in plant rhizosphere soil, resulted in a decrease of plant biomass ( Khan et al, 2021 ). We also found that heat stress can change soil available N content, to influence the absorption of nutrients by plants, brought changes to various plant physio-logical indicators ( Guo et al, 2022 ; Liu, L. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Studies have shown that heat stress significantly reduced the content of carbon, N, and phosphorus in plant rhizosphere soil, resulted in a decrease of plant biomass ( Khan et al, 2021 ). We also found that heat stress can change soil available N content, to influence the absorption of nutrients by plants, brought changes to various plant physio-logical indicators ( Guo et al, 2022 ; Liu, L. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 75%
“…The data in this section are quoted from our previous study ( Liu, L. et al, 2022 ). Compared with CK, MHS and HHS significantly increased the content of MDA (239 and 125%), H2O2 (70 and 56%), soluble sugar (149 and 139%), and the activity of CAT (138 and 93%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations